How to combat climate change? Three economic essays. - Steffen, Angela (Winter Industries, 2014)
This thesis studies the incentive compatibility of three specific strategies to reduce greenhouse gas emissions in absence of a comprehensive greenhouse gas reduction agreement and to handle the impacts of climate change, respectively. Chapter 2 investigates the incentive compatibility of insurance as an adaptation strategy. However, insurance is not only an adaptation strategy which can reduce the vulnerability of the society to the impacts of climate change, it can also serve as an instrument for incentivizing risk-reducing adaptation. Therefore, we study the interaction between risk-reducing anticipatory adaptation to climate change and insurance against climate change induced losses. More precisely, we show how the availability of different insurance contracts impacts the adaptation decision of risk-averse agents and discuss the consequences adaptation has for the insurer. Chapter 3 analyzes the incentives of developed countries to voluntarily fund adaptation and mitigation in developing countries in a non-cooperative world. Since the costs and benefits of mitigation policies occur over a long period, the discount rate plays an important role. Moreover, there is an asymmetry between discount rates of developed and developing countries. The implications of the discount rate and its asymmetry on adaptation and mitigation funding is the question we focus on in Chapter 3. Chapter 4 is considering whether voluntary eco-labeling is a suitable instrument to enhance social welfare by reducing emissions without governmental compulsion. Given the voluntary nature of eco-labels, the effectiveness in terms of reducing emissions crucially depends on firms' willingness to participate. Moreover, policy makers must take into account an eco-label's impact on competition between firms. How must policy makers, who aim at social welfare maximization, set up an eco-labeling standard taking into account the voluntariness of eco-labeling as well as competition? What are the effects of introducing an optimally designed labeling standard on emissions, producer surplus and consumer surplus? Does an optimally designed eco-label automatically lead to a cost-efficient emission reduction when firms dispose of different abatement technologies?
Keywords: Umweltschutz; Klima; Emission; Kohlendioxid; Preis; Umweltökonomie; Umweltqualität; Wirtschaftstheorie; Versicherung; Klimapolitik; Klimawandel; Treibhausgas; Emissionsminderung; Zertifikat; Steuerungsinstrument; Umweltzeichen